Extracorporeal shock wave lithotripsy: the first 50 patients treated in Britain. Issue 6476 (20th April 1985) - Wickham, J E; Webb, D R; Payne, S R; Kellet, M J; Watkinson, G; Whitfield, H N
Abstract : Fifty patients have been treated for upper tract urinary calculi by extracorporeal shock wave lithotripsy (ESWL) at the Devonshire Hospital lithotripter centre since November 1984. The average stay for an inpatient was 3 X 7 days. All patients suffered minimal postoperative discomfort and nearly all resumed normal activity within one day after discharge. Complications requiring auxiliary procedures were few. The procedure was found to be safe, cost effective, extremely well received by patients, and superior to all other methods of removing renal stones. This study confirms that treatment by ESWL is a specialised urological procedure that requires operators who are also trained in open, percutaneous, and ureteroscopic surgery and with a back up of a radiological team skilled in percutaneous renal puncture.